2013
DOI: 10.5603/cj.2013.0079
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of mortality in patients with prosthetic valve infective endocarditis: A nation-wide multicenter study

Abstract: (OR 24.5;) and high CRP (OR 1.02; 95% CI 1.00-1.03) measured on admission were independent risk associates for in-hospital mortality Conclusions: High creatinine level, poor functional status and high CRP measured on admission were independent risk associates for in-hospital mortality, whereas a NYHA class of III/IV and high CRP reflected independent risk for stroke/mortality end point. (Cardiol J 2013; 20, 3: 323-328)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
1
1
1
Order By: Relevance
“…It was shown that a high level of CRP in patients with HF III-IV FC was an unfavorable prognostic factor in patients with IE with a replaced valve (Elbey et al, 2013). These data do not agree with the results published by C.W.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…It was shown that a high level of CRP in patients with HF III-IV FC was an unfavorable prognostic factor in patients with IE with a replaced valve (Elbey et al, 2013). These data do not agree with the results published by C.W.…”
Section: Discussioncontrasting
confidence: 58%
“…Multivariant analysis showed that a high level of the marker was an independent predictor of death in patients with IE (Tyurin, 2012;Elbey et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…), neurologinės komplikacijos (16,7proc.) [16], smegenų embolai, NYHA III/IV klasės širdies nepakankamumas [22]. Kiti nurodo, kad dauguma sergančiųjų IE turi preegzistuojančią širdies ligą, tad širdies nepakankamumas gali pasunkinti sisteminę cirkuliacijos perkrovą ir sukelti nepakankamą inkstų perfuziją.…”
Section: Rezultataiunclassified